Pendampingan Pembuatan Kartu Pintar Pembelajaran Maharoh Kitabah Pada Guru TPQ Salafiyah Ar-Risalah - Zainuri Zainuri; Siti Nurjanah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this community service activity is to provide assistance to the educators/council of ustadz and ustadzah at TPQ Salafiyah Ar-Risalah regarding the making and use of smart card media to improve writing abilities and skills both in terms of khat, vocabulary, sentence structure and grammatical Arabic. This research uses qualitative methods because the object of research is focused on the process of learning Arabic in the form of the use of smart card media in writing skills both in terms of khat, vocabulary, sentence structure and grammar. With the smart card learning media, it will certainly make the students enthusiastic when learning takes place, especially after the learning activities of the students are active, enthusiastic and able to answer questions about maharoh kitabah. Assistance activities to the community in the form of PAR (Participatory Action Research) service to educators at TPQ Salafiyah Ar-Risalah Curah Putih Tegalwangi, through this smart card learning media made of cardboard and origami paper, have many benefits in learning Maharoh Kitabah and can invite students to be more enthusiastic and play an active role during the activity